The Impact of Casein Phosphopeptide-Amorphous Calcium Fluoride Phosphate on Remineralization of Caries Lesions in Relation to the Mineral Distribution within the Lesion - SaadElSayed AbdElNaby Nawaya,; Amir Hussieny Abd El Hamid Ibrahim,; Hosam Muhammed Elsayed,; Ahmed Mohamed Abu siyam,; Ahmed Ali Ezzeldine,; Nasser Mohey Shehab,; Ahmed Tharwat Al Ammary,; Hatem Abdul Monaem El bially,; Mahmoud Elsayed Fetouh,; Ahmed Ali, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Early enamel caries lesions are reversible through non-invasive approaches that enhance natural remineralization, particularly using agents like fluoride and biomimetic calcium-phosphate compounds likeCasein Phosphopeptide-Amorphous Calcium Fluoride Phosphate (CPP-ACFP). Objective: The current in vitro research aimed to assess the remineralization efficacy of CPP-ACFP on enamel caries lesions and assess the influence of baseline mineral distribution on treatment outcomes. Materials and Methods: Sixty premolar enamel samples were prepared and demineralized using a methylcellulose-based protocol to simulate early carious lesions. Specimens were randomly allocated into three groups (n=20): CPP-ACFP (MI Paste Plus), 5% sodium fluoride varnish (PreviDent®) as positive control group, and deionized water as negative control group. Interventions were applied over four days, followed by a four-day immersion in artificial saliva. Remineralization outcomes were quantitatively assessed using Transverse Microradiography (TMR), focusing on alterations in integrated mineral loss (ΔΔZ), lesion depth (ΔLD), and surface zone maximum mineral density (ΔSZmax). Results: CPP-ACFP treatment significantly improved surface zone mineral density (ΔSZmax = +11.89%) compared to fluoride varnish (+4.76%) and deionized water (+7.40%), with statistically significant variations (p = 0.01). While lesion depth reductions (ΔLD) were not statistically variation amongst the groups (p = 0.82), CPP-ACFP also demonstrated a substantial reduction in integrated mineral loss (ΔΔZ = −11.9 vol%·μm) relative to controls. Conclusions: CPP-ACFP showed significant potential in promoting enamel remineralization, increasing surface zone mineral density, and was found to be like fluoride varnish in affecting lesion depth, thus supporting its inclusion in caries management protocols.